Evaluation of time-dependent strengths of californium neutron sources by decay of 252Cf, 250Cf, and 248Cm: Uncertainties by Monte Carlo method. (January 2021) - Hila, Frederick C.; Dingle, Cheri Anne M.; Asuncion-Astronomo, Alvie; Balderas, Charlotte V.; Grande, Marianna Lourdes Marie L.; Romallosa, Kristine Marie D.; Guillermo, Neil Raymund D.
Abstract: A method for estimating source strength measurements of californium neutron sources is presented, based on the model of 252 Cf, 250 Cf, and 248 Cm decay. This is combined with the Monte Carlo method (MCM) of propagating uncertainties. Californium sources were categorized into two types: Sort–A are those with most input quantities known while Sort–B are sources with only the mass at a certain reference date known. For Sort–A, the spread of all input quantities was estimated with Gaussian distribution and the deterministic 1st order GUM uncertainty propagation is applied to validate the MCM results. While, for Sort–B with inputs that have non-Gaussian distributions, only MCM is applied to evaluate uncertainties. Results show that for californium sources that are 25 y or older, a simple 252 Cf decay correction is imprecise due to the contribution of 250 Cf and 248 Cm. The MCM was also shown to be a robust technique for uncertainty analysis that provides results for both Gaussian and non-Gaussian distributions. Moreover, the time-dependence of the contributors in the source strength and the corresponding uncertainties are presented. When exceedingly low uncertainties are not required, the calculation techniques presented in this work may serve as an alternative to actual measurements, which tend to be expensive. Highlights: A method of estimating neutron source strength was investigated. Monte Carlo method in GUM supplement 1 was used for uncertainty propagation. The consequences of the nuclear data uncertainties in literature were evaluated. The consequence of an unknown isotopic impurity content was evaluated. The consequences of unknown dates of isotopic analysis and Cm separation were evaluated.